Effect of Gender to Fat Deposition in Yaks Based on Transcriptomic and Metabolomics Analysis - Xiong, Lin; Pei, Jie; Wu, Xiaoyun; Kalwar, Qudratullah; Yan, Ping; Guo, Xian (Frontiers in Cell and Developmental Biology, 2021)
Fat deposition in yaks play an important part in survival, multiply and meat quality. In this work, the characteristic of fat deposition in male yaks (MYs) and female yaks (FYs), and the regulations of gender to yaks fat deposition were explored by mRNA-Seq and non-targeted metabolomics analyses. FYs possessed higher body fat rate (BFR) of visceral fat, fat content in longissimus dorsi (LD) and liver, and subcutaneous fat thickness (P < 0.05). The fat and cholesterol synthesis in liver, and the fat transport in FYs blood increased. The fat metabolism in yaks is the combined effect of carbohydrate, fatty acid and amnio acid metabolsim by tricarboxylic acid (TCA) cycle, and an increase of triglyceride (TG) synthesis was accompanied by an increase of steroid synthesis. The high levels of myo-inositol and cortisol (COR) (P < 0.01) activated the calcium signaling in FYs subcutaneous fat, following by the increase of adipocyte secretion, and resulted in more leptin (LEP) secretion (P < 0.01). Then the peroxisome proliferators-activated receptor (PPAR) signaling was activated by the focal adhesions and ECM-receptor interaction. Finally, the TG and steroid synthesis increased by the expression regulation of ME1, SCD, ELOVL6, DGAT2, DBI, LPL, CPT1, PLIN1, LIPA, DHCR24 and SQLE gene. Above genes can be considered as the candidate genes for yak with higher fat amount in molecular breeding in the future. This study can provide theoretical basis for improving the meat quality and breeding of yaks.